Penerapan Teknologi Tepat Guna Untuk Menunjang Proses Revitalisasi Kolam Renang Kucur Aren Di Desa Wonokerto, Wonosalam, Jombang - Dinar Pramadhani; R. Yuniardi Rusdianto (BADAN PENERBIT STIEPARI PRESS, 2023)
The Kucur Aren swimming pool is a tourist attraction located in Wonokerto Village, Wonosalam District, Jombang Regency. The Covid-19 pandemic caused this tour to be abandoned for approximately three years. This community service activity aims to provide waste bin facilities by recycling paint bucket waste as an appropriate technology that can support the revitalization process and develop the tourist attraction of the Kucur Aren swimming pool. The method used in this research is Community Based Participatory Research (CBPR) which involves the community as partners and emphasizes the values of social transformation, collaboration, and community empowerment. The result of this activity is the reopening of the Kucur Aren swimming pool as a tourist destination equipped with various supporting facilities.